FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KEDELAI DI PROVINSI SUMATERA UTARA - Rahmanta Ginting (Universitas Negeri Medan, 2015)
A soybean is a food crops and vegetable proteins source important for people in North Sumatera Province. A soybean demands increased from year to year in North Sumatera Province. It caused by several factors such as a population growth, per capita income, and change in food consumption patterns with economic growth in North Sumatera Province. Therefore, the purpose of this study is to analyze a factors that influence of soybean demand in North Sumatera Province. The data used a secondary data sourced in the form of time series from 1990 – 2013. The analysis model is a double linear regression. The result showed that the soybean price influences negative and not significant to the soybean demand, the corn price influences positive and not significant to soybean demand, while the total population and per capita income influences positive and not significant to soybean demand in North Sumatera Province.